Investigation of fibre reinforcement toward polymer production emphasizing fused deposition modelling - Idris, Mat Sahat; Oumer, Ahmed Nurye; Zulkifli, Ahmad@Manap; Mohd Ruzaimi, Mat Rejab (2018)
In this research, we want to study the effect of fibre reinforcemenrt towards the mechanical strength. We use cylinder tubes to study the effect of combining PLA(polyl Actic acid) 3D printing and carbon fibres together with PLA (3D print only) and Carbon Fibre reinforced Plastics (only). We used compression testing to determine the mechanical properties of each specimen. From the study we found out,the combined hybrid CFRP/PLA show the highest compressive strength as compared to others.